CLASSICAL ISLAMIC ART AND ARCHITECTURE - Iin Inayatul Ummah; Usnia Usnia; Suadi Saad; Endang Saeful Anwar (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Classical Islamic art and architecture have profound and functional characteristics, and are heavily influenced by the spiritual and aesthetic values ​​contained in the teachings of Islam. This article aims to explore the evolution of classical Islamic art and architecture with a focus on geometric design, calligraphy, and the cultural influences that shape both aspects. Using a literature review method, this article reviews references to relevant articles from the literature in recent years. The findings of the study show that classical Islamic architecture and art are not only representations of beauty but also the deepest Islamic beliefs and philosophies. Future generations will continue to be inspired by Islamic art and architecture, which are silent witnesses to the splendor of Islamic civilization.